Handbook of Construction Management for Instrumentation and Controls - Srinivasan, K; Vasudevan, T. V; Kannan, S; Ramesh Kumar, D (John Wiley & Sons, 2024)
Comprehensive resource discussing the effective delivery of projects to install and commission complex, high performance instrumentation and controls in process and related plantsThis book is a detailed guide discussing the many nuanced aspects required to deliver projects to install and commission complex, high performance instrumentation and controls. While standards and instrument manufacturer data are always available, the effective delivery of such projects involves much more than just fitting instruments on panels. This book digs into the specifics to provide actionable and practical guidance.This handbook includes information on:● Site administration, including planning and scheduling, site safety, and contractor permits-to-work, Keeping digital documentation up-to-date as changes occur during testing & commissioning● Material management and manpower planning, instrument calibration, controller tuning, results recording, and participation in plant commissioning exercises● Site operations, including the principles of equipment installation and testing for a huge range of instrument and control types. Documenting the results● QA & QC procedures, commissioning, and site handover, and forms and checklists that can be used on real installation and commissioning projectsWith comprehensive and highly practical coverage of the subject, This book is an essential resource for professionals working in general contractors, consulting engineers, construction managers, and specialty contractors and subcontractors.